Knowledge and perception regarding colorectal cancer among IIUM Kuantan undergraduates - Zainuddin, Norafiza; Shamri, Nur Adibah (Universiti Sultan Zainal Abidin (UNiSZA), 2018)
Colorectal cancer (CRC) is a cancer of the large intestine with high mortality and morbidity rate. According to the Malaysian National Cancer Registry Report, CRC was reported as the second most frequent cancer after breast cancer. This study was conducted to evaluate the knowledge and perception of IIUM Kuantan Campus students regarding CRC. Currently, there is no national screening program conducted by the Ministry of Health Malaysia for CRC as an early prevention in Malaysia. Despite the increase in incidence and mortality rates of CRC, emphasis on creating awareness regarding CRC among Malaysian is still lacking. Using convenience sampling method and adapted self-administered questionnaires, this cross-sectional study was conducted among the undergraduate students of International Islamic University Malaysia, Kuantan Campus. Overall, more than half of the respondents have a moderate level of knowledge and perceptions regarding CRC. Moreover, there was a significant difference between male and female respondents in terms of knowledge regarding CRC screening (p<0.001). There was also a significant difference in terms of knowledge regarding CRC between different kulliyyahs (p=0.001). However, no correlation was found between knowledge and perception regarding CRC and screening among IIUM Kuantan students. Approximately half of IIUM Kuantan undergraduate students had moderate level of knowledge and perception regarding CRC and screening. Respondents from Kulliyyah of Medicine showed higher knowledge scores compared to respondents from other kulliyyahs, probably due to the educational courses they undertook during their academic years, and to the fact that they were more familiar with the healthcare systems. Female respondents showed higher knowledge score and slightly higher perception score, which could be contributed to females being more concerned in early cancer detection than males. An overall moderate score among the science- and health-based undergraduate students suggested that it is essential to empower the young adults regarding information on colorectal cancer prevention and intention to go for screening. Effective and long-lasting promotional campaigns must be conducted to improve the level of knowledge and perceptions regarding CRC and screening, particularly to benefit the young adults in the community, and this may begin with the undergraduates.